接着剤による木造仕口の補強効果 - 飯塚 五郎蔵; 安宅 信行; Takahashi Shigeo; 立花 正敏; 榎本 裕人; 高橋 喜代志 (住宅建築研究所報, 1988)
Significance of the experiments Timber structure should be strengthened by using bolts and metal fasteners. However, in case of traditional or esthetic design of wood building, as columns and roof trusses are disclosed, exposed metal fasteners are apt to be unsightly. One of the ideas to solve this problem is to apply adhesives at the tenon-mortise joints of the construction on site. To secure final resistance (fall-safe) of the joint, L shaped metal connector could be nailed inside the wall covering. These reinforcements make a frame stiffer and stronger against lateral forces without any bearing wall or bracing. The adhesives used here should have the following properties, (1) “Open time” should be long enough for use on site. (2) Not subject to insensible any change of temperature and moisture when it is hardening. (3) Keeps ductility after setting. The author chose a modified Urethane glue for this purpose. To examine stiffness and strength of the T joint, 135 test-pieces were tested by 27 categories of tests to know the influence of, (1) species of the member, (2) sectional dimension of the member, (3) length of the tenon, (4) effect of the angle piece metal reinforcement. Test results and summary The experiments were conducted applying a lateral force to the top of the column 70 cm apart from the sill. Rigidity of the joint could be determined by measuring angle of deformation caused by the load. Results are as follows; (1) Species …HINOKI (Japanese Cypress) was the best not only in stiffness but also strength, as well as ductility. BEITSUGA (Hem-fir) followed hext a little lower, and SUGI (Japanese Cedar). (2) Sectional dimension…The wider the better in stiffness and strength especially in case of the short tenon. (3) Length of the tenon…Specimens having long tenon are 1.5 times stronger than the shorter ones. Long tenon was often broken at the last stage of the test. While short tenon was pulled out from the hole. (4) Method of fastening…Glued joints are superior to mechanical fasteners are we assumed. A series of experiments were successful. And it is effective to use metal fastener with glued joint for increasing rigidity, strength and ductility. (5) Possibility of the wood rahmen structure …According to the above mentioned results, a column with adequately fastened lateral members is expected to endure in certain extent against lateral forces caused by earthquake or heavy wind. Allowable load is estimated as 104 kg (12 cm sq.) to 141 kg (13.5 cm sq.) in case of HINOKI. And we have learned for our survey that 0.5-1.0 columns are existing in a contemporary wood house. This plan has a good chance to establish another system of house construction taking place the bearing wall system. Development of the' adhesives for this use and trial the construction in the hearest occasion should be the way to realize beautiful and strong wooden houses. 〔研究の目的と計画〕木構造接合部は金物で補強するのが最良の手段とされているが，真壁作りや伝統木造のように軸組や小屋組を意匠デザインとして扱う場合には，無神経な接合金物の露出が問題となることが多い。ここでは，在来構法の「ほぞ差し」に接着剤を使用しその剛性を高め，終局耐力を確保するためにL形金物を釘打ちすることによって構造全体の剛性・耐力を向上し，筋違いなどの耐力壁に頼らずに開放的な木造建築が安全に造れることを目的とする実験を行なった。接着剤としては，可使時間が長く，建築現場の温湿度条件に大きく影響されず，硬化後もある程度の弾力性をもつウレタン樹脂系のものを選定した。母材の樹種，断面寸法，ほぞの長さ，L形金物補強効果，などが仕口の剛性，耐力，粘り強さ等に及ぼす影響を調べるために，27種類135試験体による仕口の隅角固定度を調べる実験を行なった。〔結果と考察〕(1)母材樹種…剛性，耐力共にヒノキがまざり，ベイツガは僅かに劣り，スギ材はさらに下回る。粘り強さについても同様な傾向を示している。(2)母材断面…大い材ほど剛性，耐力に優れ，その比率は断面積比に近いようである。時に短ほぞ接着仕口の場合は剛性，耐力ともに断面が大きいほど有利である。(3)ほぞの長さ…長ほぞ差しは，短ほぞ差しにくらべて剛性，耐力，粘り強さ等すべてにおいて有利であり，特に耐力では短ほぞ差しの1.5倍以上の値を示している。(4)接合方法…接着によるものはL形金物補強のみの仕口に比べて剛性，耐力共に優れており，この実験の目的はほぼ達せられた。接着とL形全物の併用効果は，剛性，耐力，粘り強さともに明らかに認められた。(5)ラーメン化の可能性…上記の結果から，上下横架材と接合された柱1本の許容水平耐力はヒノキ材では104㎏12㎝角），141㎏（13.5㎝角）と試算された。一般の木造住宅の㎡当りの柱本数は0.5～1.0本と見積もられる。これを建築基準法の壁倍率算定法に照らして判断すると，木造住宅において筋違いを省略する構造の可能性は十分に認められる。実用化への道は現場用接着剤の開発と，実物の試作である。新しい技術を躯使した「美しくて強い木造」の実現を望むものである。